2021
DOI: 10.3390/s21113919
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nutrient Estimation and Mapping in Farmland Based on UAV Imaging Spectrometry

Abstract: Soil nutrient is one of the most important properties for improving farmland quality and product. Imaging spectrometry has the potential for rapid acquisition and real-time monitoring of soil characteristics. This study aims to explore the preprocessing and modeling methods of hyperspectral images obtained from an unmanned aerial vehicle (UAV) platform for estimating the soil organic matter (SOM) and soil total nitrogen (STN) in farmland. The results showed that: (1) Multiplicative Scattering Correction (MSC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The model based on samples of 30% SM, which is close to real soil moisture levels after irrigation in the field, showed a robust performance with the smallest RMSEP fluctuation and achieved a suitable performance with three components. Due to the presence of functional groups such as C-H, -COOH, -OH and N-H in soil organic compounds corresponding to spectral response at different wavelengths, spectral characteristics could be explained by different component numbers [9]. Thus, a model with more components is expected to describe more SOM features, improving the accuracy.…”
Section: The Prediction Of Soil Organic Matter Available N Available ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The model based on samples of 30% SM, which is close to real soil moisture levels after irrigation in the field, showed a robust performance with the smallest RMSEP fluctuation and achieved a suitable performance with three components. Due to the presence of functional groups such as C-H, -COOH, -OH and N-H in soil organic compounds corresponding to spectral response at different wavelengths, spectral characteristics could be explained by different component numbers [9]. Thus, a model with more components is expected to describe more SOM features, improving the accuracy.…”
Section: The Prediction Of Soil Organic Matter Available N Available ...mentioning
confidence: 99%
“…Hyperspectral imaging (HSI) is a non-destructive method that can provide detailed and highly resolved reflectance characteristics of target materials on different scales, and it has the advantage of capturing both spatial and spectral information [8]. Currently, spectrometry in the laboratory has been widely applied to the quantitative inversion of SOM based on the organic matter-sensitive bands that exist in the visible range of 550-770 nm and the near-infrared range of 1300-1500 nm [4,9]. Yu et al [10] found that the correlation coefficients of soil organic carbon with the bands in the near-infrared wavelengths of 747 to 1000 nm and 1010 to 1136 nm were significant at the significance level of 0.01.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum recorded by hyperspectral imaging has high wavelength resolution and covers a wide range of wavelengths. Hyperspectral cameras have been used in chemistry and biology [38][39][40][41][42] , for example in the measurement of food freshness 43,44 and in the automatic monitoring of farm products [45][46][47] . Hyperspectral imaging has also been applied in neuroscience, such as for real-time metabolic and hemodynamic monitoring of the brain in vivo [48][49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
“…Soil and plant analysis are basic techniques (classical methods) for assessing soil fertility, nutrient available content for plant nutrition, and fertilizer interventions [22,23], but they are disadvantageous in terms of time, human resources, and costs. At the same time, imaging methods based on remote sensing, UAV, or terrestrial images provide very accurate real-time information on soil quality and fertility [24,25], crops' response to fertilizer application [26,27], and plants' nutrition status [10,28,29]. The use of vegetation indices by imaging analysis can remove or mitigate disturbing factors in crop evaluation, such as differences in plant species, canopy coverage, soil background, atmospheric condition, illumination, shadowing, solar angle, etc.…”
Section: Introductionmentioning
confidence: 99%